THE ANALYSIS OF ERRORS ON INVITATION LETTERS: (A CASE STUDY OF WRITING INVITATION LETTER BY TENTH GRADE STUDENTS MAJORING MARKETING AT SMK N 1 SLAWI USED AS WRITING ASSESSMENT): (A Case Study of Writing Invitation Letter by Tenth Grade Students Majoring Marketing at SMK N 1 Slawi used as Writing Assessment) - Nurul Adhalina (Universitas Aki, 2021)
There are four aspects of English skills should be owned by English learners in order to reach communicative competence, namely Speaking, Listening, Grammar, and Writing. By viewing the facts around, we know that the achievement of writing of Indonesian students are in a shitter, either in structure a word, the use of the term, grammar, or another objectives. They still often do mistakes and errors when they writing. In line with this case, in this article the writer tries to analyze errors in tenth grade students majoring marketing in class A at SMK N 1 Slawi while they were writing invitation letters.